The Repulsive Gravitation and Errors of Einstein (Global Journal of Science Frontier Research, 2017)
Einstein rejected repulsive gravitation which Galileo and Newton also over-looked although the repulsive gravitation can be identified if one calculates the static Einstein equation for a charged particle carefully. However, Einstein believed incorrectly the speculation of unconditional validity of E = mc 2 . Because of inadequacy in pure mathematics, Einstein failed to see that the photons have gravitational energy, and his equation has no dynamic solution and that the coupling constants cannot have unique sign. Otherwise, the Einstein equation is in conflict with the notion of photons and violates the principle of causality. Einstein also failed to see a crucial error, the inconsistency between the Einstein equation and E = mc 2 . Now, experiments have proven that the gravitational force consists of three components: 1) the massmass attractive interaction, 2) the repulsive charge-mass interaction, 3) the current-mass attractive interaction. Thus, Einstein's unification is necessary, and would start another revolution in physics. A main problem in physics is, however, the incompetence of APS in pure mathematics.
Keywords: repulsive gravitation; E = mc2; charge-mass interaction